Functional areas shape indoor microbial structure and potential risks in university dormitories - Cao, Huaiyu; Ye, Hanbing; Tian, Yucheng; Zhang, Jinhong; Xie, Yongchao; Chen, Yuan; Mo, Qiuyue; Huang, Song; Tao, Yiqi; Liu, Tang (Frontiers in Microbiology, 2025)
Exposure to indoor microbes, particularly potential pathogens, poses significant health risks to occupants. While the indoor microbiome has been extensively studied in various settings, its spatial distribution in university dormitories within hot and humid climates remains poorly understood. In this study, 56 samples were collected from four functional areas (air conditioning, sink, toilet, and floor) in student dormitories in Shenzhen, China. 16S rRNA gene sequencing revealed that the indoor microbial communities were predominantly composed of human-associated genera such as Kocuria, Corynebacterium, and Staphylococcus, with marked compositional differences among functional zones. FAPROTAX predictions further identified 74 potential human pathogens, mainly linked in literature to the risks of nosocomial infections and pneumonia. Notably, a significant portion of these pathogens belongs to the genus Acinetobacter, with elevated concentrations found in air conditioning systems, suggesting their potential as reservoirs of clinically relevant microbes. Environmental variations across room functional areas significantly influenced the composition profile of the microbiome, while the impact of occupant characteristics appeared negligible. Key environmental factors, particularly temperature, played a major role in shaping both microbial and pathogen dynamics. Floor surfaces were identified as key microbial hotspots, exhibiting complex microbial networks that interacted strongly with communities from other functional areas. This underscores the floor’s vital role in maintaining connectivity within the indoor environment. The assembly processes of indoor microbial and predicted pathogen communities were both dominated by stochastic processes, with the former primarily governed by dispersal limitations and the latter by ecological drift. Overall, this study provides critical insights into the spatial distribution, environmental drivers, and assembly mechanisms of microbial and pathogen communities in university dormitories, contributing to future assessments of indoor microbial exposure and hygiene management.